Patient-related barriers to timely dialysis access preparation : a qualitative study of the perspectives of patients, family members, and health care providers - Griva, Konstadina (2020)
Rational & Objective: A key aspect of smooth transition to dialysis is the timely creation of a permanent access. Despite early referral to kidney care, initiation onto dialysis is still suboptimal for many patients, which has clinical and cost implications. This study aimed to explore perspectives of various stakeholders on barriers to timely access creation. Study Design: Qualitative study. Setting & Participants: Semi-structured interviews with 96 participants (response rate, 67%), including patients with stage 4 chronic kidney disease (n = 30), new hemodialysis patients with (n = 18) and without (n = 20) permanent access (arteriovenous fistula), family members (n = 19), and kidney health care providers (n = 9). Analytical Approach: Thematic analysis. Results: Patients reported differential levels of behavioral activation toward access creation: avoidance/denial, wait and see, or active intention. 6 core themes were identified: (1) lack of symptoms, (2) dialysis fears and practical concerns (exaggerated fear, pain, cost, lifestyle disruptions, work-related concerns, burdening their families), (3) evaluating value against costs/risks of access creation (benefits, threat of operation, viability, prompt for early initiation), (4) preference for alternatives, (5) social influences (hearsay, family involvement, experiences of others), and (6) health care provider interactions (mistrust, interpersonal tension, lack of clarity in information). Themes were common to all groups, whereas nuanced perspectives of family members and health care providers were noted in some subthemes. Limitations: Response bias. Conclusions: Individual, interpersonal, and psychosocial factors compromise dialysis preparation and contribute to suboptimal dialysis initiation. Our findings support the need for interventions to improve patient and family engagement and address emotional concerns and misperceptions about preparing for dialysis.